Catherine Booth : laying the theological foundations of a radical movement - Read, John (The Lutterworth Press, 2013)
Catherine Booth's achievements - as a revivalist, social reformer, champion of women's rights, and, with her husband William Booth, co-founder of the Salvation Army - were widely recognized in he lifetime. However, Catherine Booth's life and work has since been largely neglected. This neglect has extended to her theological ideas, even though they were critical to the formation of Salvationism, the spirituality of the movement she cofounded. This book examines the implicit theology that under girds Catherine Booth's Salvationist spirituality and reveals the ethical concerns at the heart of her s.